Associations of neighborhood environment with brain imaging outcomes in the Australian Imaging, Biomarkers and Lifestyle cohort. Issue 4 (18th August 2016) - Cerin, Ester; Rainey‐Smith, Stephanie R.; Ames, David; Lautenschlager, Nicola T.; Macaulay, S. Lance; Fowler, Christopher; Robertson, Joanne S.; Rowe, Christopher C.; Maruff, Paul; Martins, Ralph N.; Masters, Colin L.; Ellis, Kathryn A.
Abstract : Introduction: "Walkable" neighborhoods offer older adults opportunities for activities that may benefit cognition‐related biological mechanisms. These have not previously been examined in this context. Methods: We objectively assessed neighborhood walkability for participants (n = 146) from the Australian Imaging, Biomarkers and Lifestyle study with apolipoprotein E ( APOE ) genotype and two 18‐month‐apart brain volumetric and/or amyloid β burden assessments. Linear mixed models estimated associations of neighborhood walkability with levels and changes in brain imaging outcomes, the moderating effect of APOE ε4 status, and the extent to which associations were explained by physical activity. Results: Cross‐sectionally, neighborhood walkability was predictive of better neuroimaging outcomes except for left hippocampal volume. These associations were to a small extent explained by physical activity. APOE ε4 carriers showed slower worsening of outcomes if living in walkable neighborhoods. Discussion: These findings indicate associations between neighborhood walkability and brain imaging measures (especially in APOE ε4 carriers) minimally attributable to physical activity.